Committee 'E' on the Draft 5th Five Year Plan - Planning Commission (Planning Commission)
Price Rise In view of the galloping all-round rise in prices and particularly the rise in crude oil prices, the resources position should be reviewed and the plan allocations suitably recast. Evaluation Unit for Heller Implementation The Plans were being put into execution without adequate preparations and the bureaucratic set-up was incapable of undertaking the task. There was urgent need for strengthening the monitoring and evaluation units at the Centre and in the States to ensure better implementation of the Plan programmes.
India Lok Sabha Secretariat